A análise combinatória nos vestibulares militares e olimpíadas - Mourão, William Lacerda (2018)
In this work it will be studied an important topic of Discrete Mathematics, the Combinatorial Analysis that usually scare students of several undergraduate courses, as well as the high school students and the teachers who teach the subject. The purpose of the paper is to show some problems of Combinatorial Analysis and the different ways of approaching the subject, in special, at military and olimpic exams.